LAPOR EFEKTIVITAS KINERJA KEUANGAN (Studi Kasus Pada PT Indofood CBP Sukses Makmur Tahun 2020 – 2022 ) - Mei; Musfitria, Anessa; Sitanggang, Jhonson; Septiani, Ayu (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
This research aims to see how the company's performance is measured using financial ratios, most of the figures ar obtained from cash flow statement reports. The cash flow statement report shows a process of moving cash in and out of a company which is prepared to show changes in cash during a period. This research used 8 ratios and financial reports for 3 years. This results show that for 3 years the company experienced fluctuations in financial performance.